Elephantiasis and Directed Occupational Rehabilitation - Jose Maria Pereira de Godoy; Henrique Jose Pereira de Godoy; Ana Carolina Pereira de Godoy; Maria de Fátima Guerreiro Godoy (Case Reports in Vascular Medicine)
The aim of the present study was to demonstrate the cure of elephantiasis over a ten-year follow-up period and novel discoveries with directed occupational rehabilitation. A 66-year-old female patient with a history of bilateral lower limb lymphedema reported the aggravation of the condition over the years, reaching stage III (elephantiasis). The physical examination confirmed elephantiasis. The circumference of the left lower limb was 106 cm. Her body weight was 106 kilograms, height was 160 cm, and the body mass index (BMI) was 41.6 kg/m2. The patient was submitted to intensive treatment for three weeks, which led to a 21-kg reduction in weight and 66 cm reduction in leg circumference. Ten years after treatment, the patient has maintained the results with the compression stockings. Elephantiasis can be cured, although lymphedema cannot. The cure of elephantiasis depends on maintaining the treatment of lymphedema after normalization or near normalization. Directed occupational therapy stimulates the search for new activities and a life closer to normality.